MODEL PENGEMBANGAN DESAIN DIDAKTIS SUBJECT SPECIFIC PEDAGOGY BIDANG MATEMATIKA MELALUI PROGRAM PENDIDIKAN PROFESI GURU (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2014)
One of the core competencies as a mathematics teacher is pedagogy competency, i.e competency to develops curriculum competencies (enacted curriculum) in mathematics. In Mathematics Professional Teacher Education (PPG) in UPI Bandung, this pedagogy ability are trained through the workshop called the Subject-Specific Pedagogy (SSP). The purpose of this study was to develop a workshop model that are expected to be effective in encouraging PPG participants to improve pedagogic competence. This model was developed based on the theory of didactic triangle between students, teachers and course material that covers the didactic relationship (HD), the pedagogy relationship (HP) and didactic-pedagogic anticipation (ADP). By following the established procedure of this workshop, some new math learning designs produced were more effective. This shows an increase in pedagogical competence of the PPG participants. Participants weakness in terms of their material mastery can be overcome through repersonalization as an independent task, while weakness concerning their ability to predict student response can be overcome by giving participants experience in observing and reflecting. Salah satu kompetensi inti sebagai guru matematika adalah kompetensi pedagogi yaitu mengembangkan kurikulum (enacted curriculum) dalam mata pelajaran matematika. Dalam Pendidikan Profesi Guru (PPG) Matematika di Universitas Pendidikan Bandung (UPI), kemampuan pedagogi ini dilatih melalui workshop yang disebut subject specific pedagogy (SSP). Tujuan dari kajian ini adalah mengembangkan suatu model/prosedur workshop yang efektif dalam mendorong peserta PPG untuk meningkatkan kompetensi pedagoginya. Model ini dikembangkan atas dasar teori segitiga didaktik antara siswa, guru dan materi yang meliputi Hubungan Didaktik (HD), Hubungan Pedagogik (HP) dan Antisipasi Didaktik-Pedagogik (ADP). Dengan mengikuti prosedur workshop yang telah ditetapkan ini, diperoleh desain pembelajaran matematika yang baru dan efektif. Hal ini menunjukkan adanya peningkatan kompetensi pedagogik para peserta  PPG.  Kelemahan peserta akan penguasaan materi dapat diatasi melalui  pendalaman kembali (repersonalisasi) sebagai tugas mandiri, sedangkan kelemahan dalam memprediksi respon siswa dapat diatasi dengan memberikan para peserta pengalaman dalam mengobservasi dan refleksi.
Keywords: antisipasi didaktik-pedagogik; desain didaktis; hubungan didaktik; hubungan pedagogik; subject specific pedagogy; didactic design; didactic-pedagogic anticipation; didactic relationship; pedagogic relationship